Influence of heat input on the tensile properties of austenitic-ferritic welded joints - Bukvić, Aleksandar G.; Petrović, Dalibor P.; Radisavljević, Igor Z.; Dimitrić, Saša S. (Vojnotehnički glasnik / Military Technical Courier, 2022)
Introduction/purpose: During exploitation tests of gasoline storage tanks, cracks can form in an austenitic-ferrite welded joint, which can compromise the entire tank.Methods: In order to obtain a welded joint of satisfactory strength and durability, the paper analyzes the influence of heat input on the tensile characteristics of welded joints. In the current literature and practice, additional materials for welding the tank elements are selected according to the chemical compositions of the elements of basic materials, with the help of the Schaeffler diagram. In this paper, the characteristics of welded joints of gasoline storage tanks are examined, when the largest part of the tank is made of fine - grained microalloyed steel NIOMOL 490 K, while the roof part of the tank is made of austenitic steel. Slabs of these two materials were welded by the MIG process with additional material MIG 18/8/6, at different amounts of heat input.Conclusion: The analysis of the results obtained by tensile testing according to SRPS EN ISO 6892-1: 2020 standard concluded that the behavior of the joint as a whole depends on the properties of each individual part of the welded joint and their mutual influence. It was also concluded that the mutual influence is better if welding is performed with a lower amount of heat input, because then a lower degree of mixing of additional material with basic materials is achieved.
Keywords: austenitic-ferritic welded joint; strength; plasticity